Effect of Low Level Laser Therapy on Proliferation and Differentiation of the Cells Contributing in Bone Regeneration: A Systematic Review - Amid, Reza; Kadkhodazadeh, Mahdi; Ghazizadeh Ahsaie, Mitra; Hakakzadeh, Arian (Journal of Lasers in Medical Sciences, 2014)
Introduction: Low level laser therapy (LLLT) also known as photobiomodulation, is a treatment that uses low-level lasers or light-emitting diodes (LEDs) to change cellular function and is a clinically well accepted tool in regenerative medicine and dentistry. Considering the variety of laser, exposure, cells and study types, the exact effects of low level laser therapy seems to be unclear. The aim of this study was to review the data published in the field of the effects of low level laser therapy on proliferation and differentiation of the cells contributing in bone regeneration. Methods: To access relevant articles, an electronic search in PubMed was conducted from 2001 to April 2014. English language published papers on low level laser therapy were found using the selected keywords .The full texts of potentially suitable articles were obtained for final assessment according to the exclusion and inclusion criteria. Results: 240 articles were found from 2001 to April 2014. Following the initial screening of titles and abstracts as well as the final screening of full texts, 22 articles completely fulfilled the inclusion criteria of this study. Wavelength used in LLLT irradiation varied between 600 to 1000 nm with an energy density of 0.04–60J/cm2. Although almost all studies agreed on getting positive effects from LLLT, some had opposing results. Conclusion: Low level laser with low-energy density range appears to exert a biostimulatory effect on bone tissue, enhance osteoblastic proliferation and differentiation on cell lines used in in vitro studies. Despite the fact that many researches have been recently done on the effects of LLLT on different cell lines, without knowing the precise mechanism and effects, we are not able to offer a clinical treatment protocol. This paper is a beginning to help further progress and extend practical use of LLLT in future.